Answer:
14
Step-by-step explanation:
a) true
b) false
c) true
Step-by-step explanation:
<h3>let's determine the first statement</h3><h3>to determine x-intercept </h3><h3>substitute y=0</h3>
so,
8x-2y=24
8x-2.0=24
8x=24
x=3
therefore
the first statement is <u>true</u>
let's determine the second statement
<h3>to determine y-intercept </h3><h3>substitute x=0</h3>
so,
8x-2y=24
8.0-2y=24
-2y=24
y=-12
therefore
the second statement is <u>False</u>
to determine the third statements
<h3>we need to turn the given equation into this form</h3><h2>y=mx+b</h2><h3>let's solve:</h3>
8x-2y=24
-2y=-8x+24
y=4x-12
therefore,
the third statement is also <u>true</u>
If f(z)=m^z - n^z <span>and f(1)=2, f(2)=8
then
m - n = 2 so m = n + 2
m^2 - n^2 = 8
substitute </span>m = n + 2 into m^2 - n^2 = 8
so
m^2 - n^2 = 8
(n + 2)^2 - n^2 = 8
n^2 + 4n + 4 - n^2 = 8
4n = 4
n = 1
m = n + 2 = 1 + 2 = 3
so f(z) = 3^z - 1^z
if z = 1 the f(1) = 3^1 - 1^1 = 2
if z = 2 the f(2) = 3^2 - 1^2 = 9 - 1 = 8
if z = 3 the f(3) = 3^3 - 1^2 = 27 - 1 = 26
answer
f(3) = 26
Since these are parabolas with y being squared, the standard form of such a parabola with vertex at (h, k) is
<span>x = a(y - k)^2 + h </span>
<span>There are no steps. Just look at what is inside the parentheses and compare it to (y - k) with k = -3. </span>
<span>Then look at what is added and compare it to h = -1. </span>
<span>For instance, A has (y + 1) in parentheses. So k = -1. And it has -3 added, so h = -3. That would be a vertex at (-3, -1).</span>